HUBUNGAN GANGGUAN FUNGSI KOGNITIF DENGAN KADAR CD4 PADA PASIEN HIV/AIDS DI RSUD DR.M.DJAMIL PADANG - Najma Salsabila Bustari; Yuri Haiga; Vina Tri Septiana (Nusantara Hasana Journal, 2024)
Background : Cognitive impairment as found in patients with CD4 levels below 200 / ul is one of the risk factors for impaired cognitive function in HIV / AIDS patients. Objective: To determine the relationship between impaired cognitive function and CD4 levels in HIV/AIDS patients at Dr. M. Djamil Padang Hospital. Method: The scope of this research is neuroscience and internal medicine. The study will be conducted in June - September 2023. This type of research is observational analytics. The affordable population in the study was HIV/AIDS patients at Dr. M. Djamil Padang Hospital as many as 51 samples with consecutive sampling techniques. Univariate data analysis was presented in the form of frequency distribution and bivariate analysis using the kruskall-wallis test, data processing using computerized IBM version 25.0 of the SPSS program. Results: The most age was 25-49 years, which is 40 people (78.4%), the highest level of education is high schoo l/ vocational school, which is 25 people (49.0%), the most gender is male, which is 47 people (92.2%), the most CD4 levels are medium, namely 23 people (45.1%), the most cognitive function disorders are normal, namely 25 people (49.0%), and there is a relationship between impaired cognitive function and CD4 levels in HIV/AIDS patients at Dr. M. Djamil Padang Hospital (p = 0.000). Conclusion: The most age was 25-49 years, the highest level of education is high school / vocational school, the most gender is male, the most CD4 levels are medium, the most cognitive function disorders are normal and there is a relationship between cognitive function disorders and CD4 levels in HIV / AIDS patients at Dr. M. Djamil Padang Hospital